Aksi Nyata Mahasiswa KKN UNIMAS: Edukasi Bahaya Narkoba di Desa Jatidukuh Bersama Kepolisian (Jurnal Pelayanan Masyarakat, 2026)
Drug abuse remains a serious social problem, particularly among adolescents and young adults. The spread of drugs into rural areas highlights the urgent need for preventive efforts through continuous and educational approaches. This Community Service (PkM) activity aimed to increase public knowledge and awareness regarding the dangers of drug abuse through an educational program. The study employed a descriptive quantitative and qualitative approach involving 30 adolescents and young adults from a village in Mojokerto Regency. Data were collected through pre-test and post-test questionnaires, observation, and documentation. The results indicated a significant improvement in participants’ knowledge, with the average score increasing from 56.3 in the pre-test to 82.6 in the post-test. These findings demonstrate that drug abuse education is effective in enhancing community knowledge and awareness as a preventive effort against drug abuse. Therefore, similar educational programs should be implemented continuously with support from various stakeholders to promote a healthy and drug-free community.